MEMAKSIMALKAN TEKNIK KAMERA MOVEMENT DALAM PRODUKSI FEATURE “SANG TRAVELLER” - Norman Setiawan; Widyaningytas Virgo Kartika; Arif Budiman (Jurnal Ilmu Komunikasi AKRAB, 2020)
Wonosari itself can be said to be quite a large district, but most of the people of Wonosari Gunung Kidul still work as farmers and traders, the urban area in Wonosari is also not too large and there are still a lot of green rice fields that can be found in this district, Wonosari Gunung kidul. very famous for its very beautiful beach tourist attractions.The production work raises the beach features in Wonosari, Gunung Kidul, and provides information on coastal tourist attractions in Gunung Kidul. Creation of feature works that maximize camera movement techniques such as panning, tilt, track, crab.The purpose of making this event program is to provide information to the audience through audio-visuals about beach resorts in Gunung Kidul. As a cameraman, he applies camera movement techniques to take more dramatic images. As well as combining several lenses to get artistic images.